KEWENANGAN DAN KEBIJAKAN PENDIDIKAN DALAM PUSARAN OTSUS PAPUA: Studi Kasus Penyelenggaraan Pendidikan Kristen di Tanah Papua - Marit, Elisabeth Lenny (Universitas Papua, 2018)
This article aims to illustrate the specifc powers recognized and granted through the Special Autonomy Law of Papua to organize and manage the interests of the Papuan people on their own initiative based on the aspirations and basic rights of Papuans. Wider authority for the Province and people of Papua to organize the government and manage the utilization of natural resources to the greatest possible prosperity of the people of Papua in the feld of education as part of the people of Indonesia in accordance with legislation. Education policy is a part of State policy or public policy generally provided to the people of Papua. Education policy is a public policy that regulates specifc regulations relating to the absorption of resources, allocation and distribution of sources, as well as regulation of behavior in education, especiallyChristian educational institutions. The article also reveals the enactment of specifc policies based on basic values that include protection and respect for ethics and morals, basic rights of indigenous people, human rights, rule of law, democracy, pluralism and equality of positions, rights and duties as a citizen. The granting of special autonomy thus also lies in the belief that there has been a new awareness among the Papuan people to fght peacefully and constitutionally the recognition of basic rights as well as the demand for settlement of problems related to the violation and protection of the human rights of indigenous Papuans.